Species and Strain Variability among Sarcina Isolates from Diverse Mammalian Hosts - Makovska, Marie; Killer, Jiri; Modrackova, Nikol; Ingribelli, Eugenio; Amin, Ahmad; Vlkova, Eva; Bolechova, Petra; Neuzil-Bunesova, Vera (Animals, 2023)
Sarcina spp. has been isolated from the gastrointestinal tracts of diverse mammalian hosts. Their presence is often associated with host health complications, as is evident from many previously published medical case reports. However, only a handful of studies have made proper identification. Most other identifications were solely based on typical Sarcina-like morphology without genotyping. Therefore, the aim of this work was culture detection and the taxonomic classification of Sarcina isolates originating from different mammalian hosts. Sarcina-like colonies were isolated and collected during cultivation analyses of animal fecal samples (n = 197) from primates, dogs, calves of domestic cattle, elephants, and rhinoceroses. The study was carried out on apparently healthy animals kept in zoos or by breeders in the Czech Republic and Slovakia. Selected isolates were identified and compared using 16S rRNA gene sequencing and multi-locus sequence analysis (MLSA; Iles, pheT, pyrG, rplB, rplC, and rpsC). The results indicate the taxonomic variability of Sarcina isolates. S. ventriculi appears to be a common gut microorganism in various captive primates. In contrast, a random occurrence was also recorded in dogs. However, dog isolate N13/4e could represent the next potential novel Sarcina taxonomic unit. Also, a potentially novel Sarcina species was found in elephants, with occurrences in all tested hosts. S. maxima isolates were detected rarely, only in rhinoceroses. Although Sarcina bacteria are often linked to lethal diseases, our results indicate that Sarcina spp. appear to be a common member of the gut microbiota and seem to be an opportunistic pathogen. Further characterization and pathogenic analyses are required.
Keywords: microbiota; taxonomy; animals; mammalians; cultivation; Sarcina spp.